(untitled) (World Bulletin of Education and Learning, 2025)
Mental arithmetic is widely recognized as an effective tool for strengthening cognitive abilities in primary school children, particularly the processes of memory formation, retention, and retrieval. As education systems shift toward competency-based learning, the development of mental processes such as working memory, sustained attention, and flexible thinking has become a priority for preparing children for lifelong learning. Mental arithmetic, which involves rapid calculation using internal visualization strategies rather than written tools, provides a dynamic platform for stimulating brain activity, enhancing neural plasticity, and supporting the maturation of cognitive mechanisms. In primary education, this approach contributes not only to numerical literacy but also to the development of core psychological functions, including immediate, short-term, and long-term memory capacities. The psychological foundations behind mental arithmetic highlight the role of multisensory coding, imagery-based operations, hemispheric cooperation, and emotional engagement in strengthening children’s memory systems. This article explores theoretical perspectives, empirical findings, and practical implications of using mental arithmetic as a cognitive development method. It examines how systematic and interactive exercises can influence different memory stages, focusing on primary school learners’ developmental characteristics. Special attention is given to pedagogical strategies that facilitate memory growth through structured mental arithmetic activities within modern educational settings. The research emphasizes the importance of educator competencies, motivation, and supportive learning environments in achieving positive outcomes. As digital technologies increasingly integrate into classrooms, mental arithmetic remains a unique tool for preserving natural cognitive processing and improving memory through active mental work rather than technological dependency. The findings support broader efforts to implement scientifically grounded memory-enhancement techniques in primary education.